(untitled) (Biological Sciences - PJSIR, 2004)
The effect of food additives of sodium chloride (NaCl) and sodium bicarbonate (NaHCO3) was studied on the hydrolysis of phytic acid in soybean, soaked in water and in solutions of pH4 and 6 at 30°C for 6 and 12 h. Four varieties of soybean V1 (B1-080/36), V2 (AGS-62), V3 (G1-0031) and V4 (EPPS) were selected. The amount of phytic acid in V1, V2, V3, and V4 of soybean was 12 mg, 11 mg, 13 mg and 12.5 mg/g respectively. Soaking of soybean flour for 6 and 12 h in water and in pH 4 and 6 solutions have significantly reduced (P < 0.05) the levels of phytic acid. The effect of pH 6 solution was most effective, while the effect of water and pH 4 was similar in lowering the phytic acid in soybean. The presence of mixed food additives (1% NaCl + 2% NaHCO3) in water, and pH 4 and 6 solutions, reduced the level of phytic acid in soybean to 38%, 52% and 56% for 6 h, and 48%, 55% and 68% for 12 h in respective solutions. It was observed that soaking of soybean flour in pH6 solution in the presence of NaCl and NaHCO3 phytase enzyme of the flour is well activated to hydrolyse phytic acid. These results suggest that soaking with sodium chloride and sodium bicarbonate can reduce the phytic acid in soybean flour. This treatment can improve the nutritional value of the soyabean flour, which is used in various food products of dairy and confectionery etc.